Joint moments and power in the acceleration phase of bend sprinting - Judson, L. J.; Churchill, S. M.; Barnes, A.; Stone, J. A.; Wheat, J. (Journal of Biomechanics, 2020)
Joint kinetics of the lower limb (hip, knee, ankle, midfoot and metatarsophalangeal joints) were investigated during the acceleration phase of bend sprinting and straight-line sprinting. Within the bend sprinting literature, it is generally accepted that sprint performance on the bend is restricted by moments in the non-sagittal plane preventing the production of force in the sagittal plane. However, there is limited evidence in conditions representative of elite athletics performance that supports this hypothesis. Three-dimensional kinematic and ground reaction force data were collected from seven participants during sprinting on the bend (36.5 m radius) and straight, allowing calculation of joint moment, power and energy. No changes in extensor moment were observed at the hip and knee joints. Large effect sizes (g = 1.07) suggest a trend towards an increase in left step peak ankle plantarflexion moment. This could be due to a greater need for stabilisation of the ankle joint as a consequence of non-sagittal plane adaptations of the lower limb. In addition, the observed increase in peak MTP joint plantar-flexor moment might have implications for injury risk of the fifth metatarsal. Energy generation, indicated by positive power, in the sagittal plane at the MTP and ankle joints was moderately lower on the bend than straight, whilst increases in non-sagittal plane energy absorption were observed at the ankle joint. Therefore, energy absorption at the foot and ankle may be a key consideration in improving bend sprinting performance.